Rethinking Pro Bono: Students Lending a Legal Hand - Sebastian De Brennan (Legal Education Review, 2005)
Negotiation is a key skill for legal practice and one that offers a rich theoretical literature as well as opportunities for experiential learning. However it can be a challenging skill to teach both in the law school and law firm environment. Many teachers have limited time and resources and may be tempted to fall back on a fairly basic model for teaching negotiation skills. This paper outlines research that is showing new and innovative ways of teaching negotiation skills. While best practice is still evolving, there are a number of clear insights from work to date. Practical suggestions for class activities are offered including in areas such as expert observation, emotional intelligence and analogical reasoning. The authors draw on their experience teaching negotiation skills both to students and practitioners. Their experience is varied, ranging from groups of 5 to 180, and includes both law school, law firm, government, corporate and non-profit clients in Australia, New Zealand, South Africa and the U.S.A. In particular, the authors draw on experiences with small group and on-line negotiation teaching with law students at the University of Melbourne and Monash University.